St. Cyril of Alexandria : the christological controversy : its history, theology, and texts - McGuckin, John Anthony. (Vigiliae Christianae, Supplements, 1994)
St. Cyril of Alexandria: The Christological Controversy describes the turmoil of 5th century Christianity seeking to articulate its beliefs on the person of Christ. The policies of the Theodosian dynasty and the conflicting interests of the patriarchal sees are set as the context of the controversy between Nestorius of Constantinople and Cyril of Alexandria, a bitter dispute that racked the entire oecumene. The historical analysis expounds the arguments of both sides, particularly the Christology of Cyril which was adopted as a standard. Many major texts are presented in new translations, some of which have never before appeared in English. These writings are essential reading in the history of doctrine. The work will be an indispensable resource for all students of the period: theologians and Byzantinists.